Novel fuel injection strategies for PCCI operation of a heavy-duty turbocharged diesel engine. (October 2018) - Pandey, Sunil Kumar; Sarma Akella, S.R.; Ravikrishna, R.V.
Highlights: Novel method of air-assisted injection of diesel in intake manifold for PCCI. Air-assisted injection combined with optimized early injection strategy. Simultaneous & substantial NOx and soot reduction achieved at partial load. Abstract: Towards the objective of achieving benefits of the Premixed Charge Compression Ignition (PCCI) mode in a multi-cylinder, turbocharged, common-rail, direct-injection, heavy-duty diesel engine, simulations were first conducted to assess improvement in in-cylinder charge homogeneity by several strategies. These strategies include multiple injections, Port Fuel Injection (PFI), and combination of PFI and Early Direct Injection (EDI). The maximum Uniformity Index (UI) achieved by EDI was 0.78. The PFI strategy could achieve UI of 0.95; however, majority of the fuel remained trapped in the port after valve closure. This indicated that except EDI, none of the above-mentioned strategies could help achieve the benefits of the PCCI mode. An optimized EDI (OptimEDI) strategy gave 20% NOx and soot reduction over the conventional CI mode. Although this strategy gave encouraging results, there was a need for more substantial reduction in emissions. Hence, a novel concept of utilizing Air-assisted Injection (AAI) into the air intake was employed. Experiments were carried out with AAI and combination of OptimEDI. Results with 48% Exhaust Gas Recirculation (EGR) and 5–10% of fuel injected using AAI gave substantial reduction in NOx and soot emissions at the part-load condition of the engine.